2006
DOI: 10.1038/sj.onc.1210120
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of chemokine receptor CXCR4 by tumor suppressor p53 in breast cancer cells: implications of p53 mutation or isoform expression on breast cancer cell invasion

Abstract: Chemokine receptor CXCR4 and its ligand CXCL12 are suggested to be involved in migration, invasion and metastasis of breast cancer cells. Mutation of the tumor suppressor gene p53 in breast cancer is associated with metastasis and aggressive clinical phenotype. In this report, we demonstrate that wild type but not the dominant-negative mutant (V143A) or cancer-specific mutants (R175H or R280K) of p53 repress CXCR4 expression. Recently described cancer-specific p53 isoform, D133p53, also failed to repress CXCR4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 34 publications
6
69
0
1
Order By: Relevance
“…Chemokine receptors, including CXCR4 have a critical role in metastasis, and that CXCR4, in particular, is a key receptor in the crosstalk between tumor cells and their environment (Burger and Kipps, 2006). CXCR4 expression increases progressively with increasing malignant potential, and higher expression is associated with lymph node positivity, hormone receptor negativity, Her2 overexpression and poor survival in breast cancer (Cabioglu et al, 2005;Mehta et al, 2007), and that CXCR4 can act as a biomarker for metastasis (Cabioglu et al, 2005). Interestingly, CXCR4 has been shown to be regulated by NF-kB (Palkowitsch et al, 2008) and p53 (Mehta et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemokine receptors, including CXCR4 have a critical role in metastasis, and that CXCR4, in particular, is a key receptor in the crosstalk between tumor cells and their environment (Burger and Kipps, 2006). CXCR4 expression increases progressively with increasing malignant potential, and higher expression is associated with lymph node positivity, hormone receptor negativity, Her2 overexpression and poor survival in breast cancer (Cabioglu et al, 2005;Mehta et al, 2007), and that CXCR4 can act as a biomarker for metastasis (Cabioglu et al, 2005). Interestingly, CXCR4 has been shown to be regulated by NF-kB (Palkowitsch et al, 2008) and p53 (Mehta et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 expression increases progressively with increasing malignant potential, and higher expression is associated with lymph node positivity, hormone receptor negativity, Her2 overexpression and poor survival in breast cancer (Cabioglu et al, 2005;Mehta et al, 2007), and that CXCR4 can act as a biomarker for metastasis (Cabioglu et al, 2005). Interestingly, CXCR4 has been shown to be regulated by NF-kB (Palkowitsch et al, 2008) and p53 (Mehta et al, 2007). Overexpression of DN-IkBa in breast cancer cells resulted in reduced expression of CXCR4, and a corresponding loss of SDF1a-mediated migration in vitro (Helbig et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it should be noted that CXCR4 transcriptional regulation also includes HIF-and hypoxiaindependent mechanisms. [52][53][54] In FSGS, the primary pathology may be of direct glomerular origin whereas narrowing of the afferent blood vessels with consecutive glomerular hypoxia may be a central mechanism in NSC. Nuclear HIF1␣ in podocytes of NSC biopsy specimens can be seen as a biological indicator for hypoxia-associated transcriptional processes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that p53 is involved in the control of motility, invasion and metastasis of cancer cells through regulating several molecular signaling pathways including RhoA-ROCK pathway, 15 SDF-1/CXCL12, 16 CXCR4. 17 Although p53 mutation is known to occur in approximately 50% of human cancers, and the roles of p53 in cancer development and progression have been extensively studied and well appreciated, how loss of p53 function contributes to cancer invasion and metastasis has not been fully understood. In the current study, we demonstrated that wild-type p53 negatively modulates the protein level of EMMPRIN through the lysosomal degradation pathway, and downregulation of EMMPRIN by p53 suppresses invasive potential of cancer cells.…”
Section: Introductionmentioning
confidence: 99%